T cell development in CD8-/- mice. Thymic positive selection is biased toward the helper phenotype. - Bachmann, M; Oxenius, A; Mak, T; Zinkernagel, R (1995)
The CD4 and CD8 molecules are involved in T cell differentiation and activation. Nevertheless, efficient thymic maturation of helper T cells has been shown in the absence of the CD4 molecule. These CD4-deficient helper T cells expressed alpha beta-TCR and were able to control Leishmania infections and to mediate Ab class switch. Using mice deficient for the CD8 alpha-chain, we investigated whether a similar cytotoxic T cell population was generated in the absence of the CD8 coreceptor. A CD8-deficient cytotoxic T cell population corresponding to the described CD4-deficient helper T cell population was virtually absent both functionally and physically. These results support the idea that thymic maturation is asymmetrical and strongly biased toward the helper phenotype.